Jean-Luc Marion's Reading of Dionysius the Areopagite. Hermeneutics and reception history - Zachhuber, J (Bloomsbury Publishing, 2011)
The aim of this essay is to elucidate Jean-Luc Marion’s reading of the fifth-century theologian known as Pseudo-Dionysius the Areopagite. This has been done before, but it seems to me that existing studies leave room for further investigation. Specifically, I contend that Marion’s interpretation of Dionysius’s thought, in order to be properly understood, needs to be placed within the context of the latter’s reception history. I shall argue that such a focus on reception history, which is both the foundation of individual engagements with a text and their product, integrates creative and receptive aspects of reading better than the notion of an ahistorical encounter between a contemporary reader and a 1500-year-old text. In order to develop this argument, I shall start with some remarks about the ambiguities of the modern idea of reading past texts. From those I shall move on to consider Marion’s engagement with the Dionysian corpus and argue in the third and final part of this paper that (and how) a consideration of the historical context of Marion’s interpretation can help elucidate his appropriation of those Patristic texts for a remarkable and, for all its internal tensions, immensely fruitful theological project.